ANALISIS YURIDIS ATAS KEWENANGAN DAN PERTANGGUNG JAWABAN NOTARIS PADA PENDAFTARAN SURAT DIBAWAH TANGAN - ROBEIND CHANDRA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Notaris Dr. Henry Sinaga, SH MKn2.  Notaris Dr. Tony, SH, MKn3.  Notaris Dr. Suprayitno, SH, MKn Based on the results of the study it can be seen that the practice of registration by a notary public, that registration is only registered in a special book provided by the notary for that and each page is filled with initials with a position stamp regarding the making of an agreement. So that the deed under the hand that has been registered provides information for the judge regarding the date of registration related to the agreement. In this case the parties whose names are listed in the letter can no longer say that the parties or one of the parties do not know the contents of the letter, because the contents have been made / agreed and signed by the parties before coming to the notary office then the letter can only be only registered in a special book is provided by the notary for that and each page is affixed with a position stamp. The notary's responsibility for the truth of the deed under the hand that is registration is imperfect. Keywords: Registration, Deed Under Hands, Proof